An Isolable Radical Anion of an Organosilicon Cluster Containing Only σ Bonds1. (26th May 2015) - Otsuka, Kyohei; Matsumoto, Naozumi; Ishida, Shintaro; Kyushin, Soichiro
Abstract The radical anion of octa‐tert‐butyloctasilacubane was generated and isolated. The EPR spectrum showed the satellites due to the tertiary 13C nuclei of the eight tert‐butyl groups. The X‐ray crystallographic analysis showed that the SiSi bonds are shortened and the SiC bonds are elongated compared with those of octa‐tert‐butyloctasilacubane. These results are well explained by the distribution of an unpaired electron in the singly occupied molecular orbital (SOMO).